Fostering Share&Charge through proper regulation. Issue 1 (March 2018) - Vanrykel, Fanny; Ernst, Damien; Bourgeois, Marc
This article studies the emergence of Share&Charge, a German platform that organizes the sharing of charging stations for electric vehicles (EVs) and the billing for the energy transactions. Share&Charge follows a peer-to-peer fashion, enabling direct transactions between charging station owners and EV drivers. On the demand side, the platform, with its interactive map, makes it possible for EV owners to find a charging station in the most suitable location, for instance, at their place of work or where they live. On the offer side, Share&Charge enables station operators (private individuals or companies) to rent their charging stations and eventually to sell the electricity they produce. Charging tariffs within the charging station network are determined by the charging station operators themselves, but the platform provides indicative tariffs. Launched in September 2017, Share&Charge follows other initiatives, such as the French platforms Wattpop and ChargeMap, and the Swedish Elbnb. Share&Charge's network is already proven to be successful with German citizens. Share&Charge adds certain elements of value at different stages of EV utilization. First, this model allows for a co-financing of charging infrastructures by individuals and businesses in the private sector by sharing the infrastructure costs among EV drivers. Besides the purchase price of EVs, the implementation of charging infrastructures and their financing represent a significant barrier to the rise of e-mobility. Share&Charge helps remove this obstacle without adding a further burden on the governmental budget. In addition, this approach follows the "user pays principle, " which engages in fair and effective financing. Second, the platform increases decentralized production value and facilitates its expansion. It also helps in avoiding grid congestion and energy loss, as well as increasing flexibility within the electricity market. Third, data use enables the optimization of energy demand and supply, and the optimal determination of tariffs, although these remain facultative. Models like Share&Charge could thus positively impact energy policy by tackling several upcoming obstacles associated with the development of EVs and decentralized energy production capacities. However, new forms of network structures (decentralized networks, sharing economy) and new actors (prosumers, platforms, etc.) also raise regulatory challenges. This article presents some of the legal issues associated with the development of models like Share&Charge. In particular, we study the tax framework applicable to this model, assuming that as such, it would be introduced into the Belgian market.